Program Edukasi K3 dan Stretching Exercise dalam Menurunkan Nyeri Ekstremitas Atas pada Pekerja Sektor Pengolahan Makanan - Santoso, Dwi (Pakis Journal Institute, 2026)
Musculoskeletal disorders are a common occupational health problem among workers in the informal sector, including those in the food processing industry. Manual work activities, such as prolonged standing, bending, and repetitive movements of the shoulders, arms, and wrists, can increase the risk of upper extremity pain. Furthermore, workers' poor understanding of Occupational Safety and Health (OHS) principles and work ergonomics can exacerbate these conditions. Therefore, preventive measures are needed through an OHS education program accompanied by stretching exercises. This activity aims to reduce upper extremity pain while increasing workers' knowledge of OHS. The method used was a pre-experimental design with a one-group pre-test and post-test approach involving 10 food processing workers aged 22–60 years. Pain levels were measured using a Numeric Rating Scale (NRS), while respondents' knowledge was assessed through pre-test and post-test questionnaires. The results showed a decrease in upper extremity pain levels after the intervention, with the average pain score before the intervention ranging from 4–5 to around 3 after the intervention. Furthermore, there was an increase in respondents' knowledge of occupational health and safety (K3), as evidenced by the increase in the number of correct answers, from an average of 3–4 to around 9–10 after the education.